Using aligned poly(3-hexylthiophene)/poly(methyl methacrylate) blend fibers to detect volatile organic compounds. (19th March 2018) - Chan, Shun-Hsiang; Lin, Tz-Feng; Wu, Ming-Chung; Chen, Shih-Hsuan; Su, Wei-Fang; Lai, Chao-Sung
Abstract: In this study, we developed a novel sensing material fabricated using a poly(3-hexylthiophene) (P3HT)/poly(methyl methacrylate) (PMMA) blend fiber on a glass substrate. The sensing materials can easily be used for sensing toluene vapor detected from extinction spectral changes. The extinction spectra variation is noted from the absorption of volatile organic compounds in a highly specific surface area of fibrous coating. An electrospinning technique is applied to generate a nonwoven structure and uniaxial orientation by fibrous coating. The response of the uniaxially orientated fibrous film is even improved at several toluene vapor concentrations. The best detection limit of this well-aligned fibrous film is up to 200 ppm for toluene vapor.